Measurement of temperature of molten zone at the directional crystallization of blades of the gas-turbine engine - Markin, M.O.; Markina, O.M.; Kushchovyi, S.M. (Успехи физики металлов, 2017)
The review article is devoted to detailed analysis of known methods and ways for measuring the temperature parameters in the area of directional solidification of the melt of the rotor blades of gas-turbine engines. The analysis of existing methods of temperature control such as contactless methods and contact ones is made. As found, in further progress and development of devices and methods of temperature analysis, priority belongs to pyrometry. Relied on the advantages and disadvantages of existing methods, it is determined that the solution of this problem is possible with use of spectral and imaging pyrometry. Обзорная статья посвящена основательному анализу известных методов и способов измерения температурных параметров в зоне расплава при направленной кристаллизации рабочих лопаток роторов газотурбинных двигателей. Проведён анализ существующих методов контроля температуры как контактных, так и бесконтактных. Установлено, что в дальнейшем прогрессе и развитии приборов и способов анализа температуры приоритет принадлежит пирометрии. Опираясь на недостатки и преимущества существующих методов, определено, что решение поставленной проблемы возможно за счёт использования спектральной и телевизионной пирометрии. Оглядову статтю присвячено ґрунтовній аналізі відомих метод і способів міряння температурних параметрів у зоні розтопу за спрямованої кристалізації робочих лопаток роторів газотурбінних двигунів. Проведено аналізу наявних метод контролю температури як контактних, так і безконтактних. Встановлено, що у подальшому проґресі та розвитку приладів і способів аналізи температури пріоритет належить пірометрії. Спираючись на недоліки та переваги наявних метод, визначено, що розв’язання поставленої проблеми можливе з допомогою використання спектральної та телевізійної пірометрії.